SMKS X Sidoarjo Inventory: Website-Based Facility Information System: Inventarisasi SMKS X Sidoarjo : Sistem Informasi Sarana Berbasis Website - Tubira, Muchamad Firmansyah; Suprianto (Universitas Muhammadiyah Sidoarjo, 2024)
SMK X Sidoarjo is an educational institution that has received support from the Education Office as an Industrial Revolution 4.0 school. SMK X Sidoarjo needs to take advantage of technological advances. School infrastructure is very important for the process of education, monitoring and effective inventory management. Therefore, researchers built an information system